Brilliant bodies : fashioning courtly men in early Renaissance Italy - McCall, Timothy (The Pennsylvania State University Press, 2022)
"Explores the relationship between fashion and power in Renaissance Italy, focusing on visual art and culture and the nature of aristocratic masculinity and patriarchal authority"--